Experimental Study of Quality of Plastic Details of the Oil-Field Equipment (International Journal of Innovative Research in Computer Science & Technology, 2021)
ABSTRACT- In article quality of plastic details of the oil field equipment depending on modes of production of their  various constructions and composition of press materials was  reviewed. By adjusting the operating parameters during  production of details are defined quality indicators: tensile  strength, hardness of details and others. Mathematical  dependencies between quality indicators (shrinkage and  strength) of details and processing temperature are established.  The determination of optimal production rejimes for plastic  products requires experimental and theoretical researches, the  volume of which increases significantly with the number of  shapes and sizes. The organization and conduct of such  researches with a view to developing recommendations for the  production and operation of these products can lead to a  significant expenditure of material and labour resources. In  practice of designing of machine details and the equipment for  assessment the hazard of a tense situation usually use not  criteria of strength, only the safety margin coefficient or  equivalent stress. Methods of calculation of equivalent stress  are considered on the basis of a method of calculation of  equivalent stress is developed that is necessary for practice.
Keywords: Elastic deformation; Phenoplast; Plastic details; Specific energy; Strength